Genetic Risk Assessment for Women with Epithelial Ovarian Cancer: Referral Patterns and Outcomes in a University Gynecologic Oncology Clinic - Petzel, Sue V. (J Genet Couns, 2013)
Little is known about genetic service utilization and ovarian cancer. We identified the frequency and outcome of genetic counseling referral, predictors of referral, and referral uptake for ovarian cancer patients. Using pathology reports, we identified all epithelial ovarian cancer patients seen in a university gynecologic oncology clinic (1/04–8/06). Electronic medical records (EMR) were used to document genetic service referral, time from diagnosis-to-referral, point-in-treatment at referral, personal/family cancer history, demographics, and genetic test results. Groups were compared using chi-squared and Fisher’s exact test for categorical variables and t-tests for continuous variables. The study population consisted of 376 women with ovarian cancer, 72 (19 %) of who were referred for genetic counseling/testing, primarily during surveillance. Of those referred, 42 (58 %) had personal or family genetic counseling and 34 (47 %) were ultimately tested or identified due to known family mutation. Family history and prior cancer were associated with referral. Family history, living in a larger community, higher-stage disease, and serous histology were associated with undergoing genetic counseling. Risk assessment identified 20 BRCA1/2 (5.3 %) and 1 HNPCC (0.3 %) mutation carriers. Based on recent estimates that 11.7–16.6 % of women with ovarian cancer are BRCA carriers and 2 % are HNPCC carriers, results suggest under-identification of carriers and under-utilization of genetic services by providers and patients. Interventions to increase medical providers’ referrals, even in a specialized oncology clinic, are necessary and may include innovations in educating these providers using web-based methods. Ease of referral by the introduction of an electronic cancer genetic referral form represents another new direction that may increase genetic risk assessment for high-risk women with ovarian cancer.